Plasticity in the trophic niche of an invasive ant explains establishment success and long‐term coexistence. Issue 5 (22nd March 2021) - Balzani, Paride; Vizzini, Salvatrice; Frizzi, Filippo; Masoni, Alberto; Lessard, Jean‐Philippe; Bernasconi, Christian; Francoeur, André; Ibarra‐Isassi, Javier; Brassard, François; Cherix, Daniel; Santini, Giacomo
Abstract : Invasive species are one of the main threats to biodiversity worldwide and the processes enabling their establishment and persistence remain poorly understood. In generalist consumers, plasticity in diet and trophic niche may play a crucial role in invasion success. There is growing evidence that invasive ants, in particular, occupy lower trophic levels in their introduced range compared to the native one, but evidences remain fragmented. We conducted stable isotope analysis at five locations distributed on two continents to infer the trophic position of the invasive ant Formica paralugubris in the native and introduced part of the range. This species forms large colonies and can be a voracious predator while feeding on sugar‐based resources as well. Whereas native populations had trophic positions comparable to that of an omnivore, the introduced populations varied from being honeydew specialists to top predators, or omnivore. Where other ant species co‐occurred, there was no overlap in their trophic niches, and F. paralugubris occupied the lower position, suggesting that trophic displacement may enable the coexistence of different ant species. Taken together, our results suggest that shifts in diet associated with changes in the trophic niche of introduced species might mediate invasion success and enable long‐term coexistence with native species.